Association between the weight-adjusted-waist index and abdominal aortic calcification in United States adults: Results from the national health and nutrition examination survey 2013–2014 - Xie, Feng; Xiao, Yuan; Li, Xiaozhong; Wu, Yanqing (Frontiers in Cardiovascular Medicine, 2022)
Background: Abdominal aortic calcification (AAC) is recognized as a strong predictor of cardiovascular disease (CVD) events. This study aimed to evaluate the association between weight-adjusted-waist index (WWI) and AAC in US adults aged ≥40 years. Methods: Data were derived from the 2013-2014 National Health and Nutrition Examination Survey (NHANES). WWI was calculated as waist circumference divided by the square root of weight. AAC scores were quantified by the Kauppila scoring system, and severe AAC was defined as an AAC score ≥ 6. Weighted multivariable regression analysis and subgroup analysis were performed to evaluate the relationship between WWI with AAC scores and severe AAC. The restricted cubic spline model was used for the dose-response analysis. Results: A total of 2,772 participants were included with the mean WWI of 11.17 ± 0.73 cm/√kg and mean AAC score of 1.48 ± 3.27. The prevalence of severe AAC was 9.64%. WWI was positively associated with higher AAC scores [β = 0.95, 95% confidence interval (CI): 0.65-1.25, P <0.001] and increased risk of severe AAC [odds ratio (OR) = 1.82; 95% CI: 1.20-2.75; P = 0.005]. A nearly linear relationship between the WWI and the odds of severe AAC was found after adjustment for multiple potential covariates (P for nonlinear = 0.625). Subgroup analysis indicated that the association between WWI and AAC was similar in different population settings. Conclusion: Higher WWI was associated with higher AAC score and increased risk of severe AAC in US adults. Further studies are needed to confirm this relationship.